ANALISIS POLA KONSUMSI RUMAH TANGGA PENGRAJIN SONGKET DI KOTA PALEMBANG - Lisnini Lisnini; Purwati Purwati (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
The research was conducted to examine the consumption patterns of mothers single parents in the village craftsmen songket 30 ilir which is the center of the city of Palembang songket industry. The population size is songket 94 craftsmen, from the number of samples was taken using a purposive sampling technique. The results showed that the consumption patterns of mothers craftsmen more food consumption amounting to Rp 606,653.223, - compared to non-food consumption, in which non-food consumption in an independent variable does not include the non-food consumption will be decreased by Rp 11.341.966, -. Food consumption will decline if education and increased investment, while non-food consumption will be reduced if women artisans to increase investment. Conclusion The results of this study of food consumption was higher than non-food consumption.